Web-Based Labor Scheduling At Ekasakti University Padang - Hadi, Harry Setya; Weriza, Jusmita; putri, viola zulmi (Jurnal Manajemen Teknologi Informatika, 2023)
This system design aims to produce a labor scheduling information system at Ekasakti University Padang and produce applications that can be implemented. The system development method used in this research is SDLC (System Development Life Cycle). System design tools use UML with several diagrams, including a use case diagram, a class diagram, a sequence diagram, and an activity diagram. The result of this research is to produce a labor scheduling application at Ekaskti Padang University that can facilitate managing the labor schedule so that there is no problem in inputting the labor schedule.